Survival With Lenvatinib for the Treatment of Progressive Anaplastic Thyroid Cancer: A Single-Center, Retrospective Analysis - Kim, Soo Young; Kim, Seok-Mo; Kim, Jun Won; Lee, Ik Jae; Jeon, Tae Joo; Chang, Hojin; Kim, Bup-Woo; Lee, Yong Sang; Chang, Hang-Seok; Park, Cheong Soo (Frontiers in Endocrinology, 2020)
Background: Survival rates for anaplastic thyroid cancer (ATC) have not improved in the past four decades; however, preliminary clinical data indicate that lenvatinib may provide efficacy benefits for patients with ATC. This real-world study aimed to define the potential role of lenvatinib in ATC by examining the impact of treatment administered alongside existing therapies. Methods: This was a retrospective, single-center analysis of Korean patients with confirmed ATC who received lenvatinib between October 2015 and February 2018. Eighteen patients were included (mean ± standard deviation age, 64.9 ± 11.1 years; 61.1% female). Six [33.3%] had resectable disease that progressed after a combination of surgery, radiotherapy, and chemotherapy, and 12 [66.7%] had unresectable disease that progressed after radiation treatment and chemotherapy. Study endpoints were overall survival (OS) and change in volume of the largest tumor assessed via imaging. Results: Median OS for the 18 lenvatinib-treated patients was 230 days (range 64–839 days). Survival rates at 6 months and 1 year were 61.1% and 22.2%, respectively. Three patients (16.7%) survived beyond one year; 15 patients died, of whom four (26.7%) had local disease and 11 (73.3%) had distant metastasis. Two patients (11.1%) had tumor volume increases of 9%–10%. The other 16 patients (88.9%) had tumor volume reductions of 2%–69%. Six patients (33.3%) had tumor volume reductions ≥50%. Conclusions: In patients with ATC who had progressed on prior therapy, addition of lenvatinib could improve survival duration and reduce tumor volume. Further studies of lenvatinib in ATC are warranted.